Using Cervical Dilation to Predict Labor Onset: A Tool for Elective Labor Induction Counseling - Panelli, Danielle M.; Robinson, Julian N.; Kaimal, Anjali J.; Terry, Kathryn L.; Yang, Jiaxi; Clapp, Mark A.; Little, Sarah E. (American Journal of Perinatology, 2019)
Objective To evaluate whether cervical dilation predicts the timing and likelihood of spontaneous labor at term.Study Design This was a retrospective cohort of nulliparous women with singleton pregnancies who delivered at term from 2013 to 2015. Outpatient cervical examinations performed after 37 weeks and prior to labor onset were collected. Survival analysis was used to analyze time to spontaneous labor with cervical dilation as the primary predictor, modeled as continuous and categorical variables (<1 cm, 1 cm, >1 cm).Results Our cohort included 726 women; 407 (56%) spontaneously labored, 263 (36%) were induced, and 56 (8%) had an unlabored cesarean delivery. Women with >1-cm dilation were three times more likely to spontaneously labor (adjusted hazard ratio [aHR]: 3.1; 95% confidence interval [CI]: 2.4–4) than those with <1-cm dilation. At 39 weeks, 60% of women with >1-cm dilation went into spontaneous labor as compared with only 28% of those with <1-cm dilation (aHR: 2.9; 95% CI: 2–4.4).Conclusion In our cohort of nulliparous women at term, those with cervical dilation > 1 cm were significantly more likely to go into labor in the following week. This information can aid in counseling about elective induction of labor.
Keywords: cervical dilation; elective induction; labor